Հպարտության և փառամոլության թեման Ժան-Պոլ Սարտրի «Սատանան և տեր Աստված» պիեսում - Մայիլյան, Ալվարդ; ԵՊՀ արտասահմանյան գրականության ամբիոն (Արմավ հրատ.)
Sartre’s works, such as the novel “Nausea”, the philosophical work “Being and Nothingness”, the dramas “Flies”, “No Exit” and partly the novel “The Roads of Freedom”, are among the biggest manifestations of existentialism. The purpose of the article is to reveal the image of the protagonist of the play “The Devil and the Good Lord”, Goetz, using the concepts of pride and vanity. Sartre describes the moral adventure of man through Goetz. The isolated character tries to start a human struggle against other people. Goetz turns away from the Lord in order to present himself to the world of people. He discovers a new form of self-destruction and renounces the eternal pretence. The whole essence of Goetz’s character revolves around a tragic conflict in which he tries to maintain isolation from people while secretly striving for love and acceptance. Goetz thinks he is free to do evil, but in doing so, his personality is defeated. This is his vanity. But Goetz’s pride is an illusion, because his stubbornness is only external, he acts as if he is not a master of his craft. The Sartre hero, proud of his loneliness, actually only accepts the condition set by society and waits for the recognition. Like many other dramatic characters created by Sartre, he exists in the eyes of others, God or other people, and thus reveals himself. The extremely cruel warrior Goetz is the best captain in all of Germany, whose fame reigns in the city of Worms as a silent threat of destruction in the first act of the play. However, in Sartre’s play, the priority is to understand Goetz in the eyes of other characters who see him, know him, and associate him with his monstrous “nature”. The fact that Goetz appears only in the second scene of the play can be considered a dramatic device by which Sartre tried to make Goetz the center of the conflict. The main topic of discussion for others is this newcomer, who personifies the plot knot and is the basis of dramatic actions. It is precisely because of the negative nature of these social values that the image of Goetz was formed: this is connected with the fate that awaits him on stage, because the hero of the Devil and Lord considers himself unique. Goetz does not look at the world through an optical device, but at every step he is tempted by the reflection of his image, inspired by other people’s eyes, in which he is doomed to accept himself. Before entering the stage, he has already been assigned a place in a world where a person never thinks about getting rid of himself before the final transformation. Произведения Сартра, такие как роман «Тошнота», философский труд «Бытие и ничто», драмы «Мухи», «За закрытыми дверями» и отчасти роман «Дороги свободы», относятся к числу высших проявлений экзистенциализма. Цель статьи – раскрыть образ главного героя пьесы «Дьявол и Господь Бог» Геца с помощью понятий гордыни и честолюбия. Сартр представляет нравственные приключения человека через Геца. Изолированный герой пытается начать человеческую борьбу против других людей. Гец отворачивается от Бога, чтобы предоставить себя миру людей. Он открывает для себя новую форму саморазрушения и отказывается от вечного притворства. Вся суть характера Геца вращается вокруг трагического конфликта, во время которого он пытается сохранить изоляцию от людей, одновременно тайно стремясь к любви и принятию. Гец думает, что он свободен творить зло, но тем самым его личность терпит поражение. Это его честолюбие. Но гордыня Геца — иллюзия, потому что упорство у него только внешнее, он действует так, как будто он не мастер своего дела. Гордый своим одиночеством сартровский герой на самом деле лишь принимает поставленное обществом условие и ждет его признания. Как и многие другие драматические персонажи Сартра, он существует в глазах остальных, Бога или других людей, и таким образом раскрывает сам себя. Чрезвычайно жестокий воин Гец — лучший капитан во всей Германии, чья слава царит в городе Вормс как немая угроза разрушения в первом акте пьесы. Однако в пьесе Сартра приоритетным является понимание Геца в глазах других героев, которые его видят, знают, связывают с его чудовищной «натурой». Тот факт, что Гец появляется только во второй сцене пьесы, можно считать драматическим приемом, с помощью которого Сартр пытался сделать Геца центром конфликта. Главной темой обсуждения для окружающих является этот новичок, который и олицетворяет собой сюжетный узел и является основой драматических действий. Именно из-за негативного характера этих социальных ценностей сформировался образ Геца: это связано с судьбой, которая ждет его на сцене, потому что герой Дьявола и Бога считает себя уникальным. Гец не смотрит на мир через оптический прибор, но на каждом шагу его искушает отражение своего образа, навеянное чужими глазами, в которых он обречен принять себя. Перед выходом на сцену ему уже отведено место в мире, где человек никогда не думает о том, чтобы избавиться от себя до окончательного преображения․
Keywords: Արտասահմանյան գրականություն